Community-based health insurance scheme as a way forward in health financing in Nigerian rural areas of Sokoto State - Harun, Azhar; Abdulwaheed A., Salihu; Badamasi, Ibrahim; Ibrahim, T, Garba (2014)
Health financing in most of Sub Saharan Africa is based on out-of-pocket payment from the rural dwellers.This out-of-pocket payment has caused lot of health problems such as premature deaths, maternal problems, deficiencies in health issues in Sub Sahara countries.This paper examines issues relating to health financing in Nigerian rural areas in order to encourage people in SSA to implement Community-Based Health Insurance Scheme in the rural areas.This is significant because it provides a chance for the people to be out of poverty as a result of high money paid whenever they are assessing health care through out-of-pocket payment at the point of service delivery. This scheme is a new area of health financing in the developing countries supported by the World Health Organization (WHO), World Bank (WB) and International Labor Organization (ILO) among others. Few of the SSA countries like Ghana, Mali and Burkina Faso are doing well using the scheme to finance health care delivery in the rural areas.In Nigeria, this concept of community-based health insurance plan is a new development. So, effort should be made to create awareness about this laudable project.The management of the CBHIS should focus on the rural dwellers on one hand, and government should provide enabling laws on the other.